Accessibility And Competence Toward Zakat Financial Accountability Moderate By Internal Control - Aqilla Rahmah; Dwi Astarani Aslindar; Arum Pujiastuti (JAS (Jurnal Akuntansi Syariah), 2023)
This research examines the influence of financial report accessibility and human resource competency on zakat financial accountability with internal control as a moderating variable. This research is quantitative research by processing primary data using a questionnaire. The population of this research is all 268 executive and supervisory agency employees from 35 Lazismu regional offices in Central Java. Sample selection was carried out using a purposive sampling method so that 120 research samples were obtained. The data analysis technique used in this research is the quantitative structural equation modeling-partial least squares (SEM-PLS) analysis method using SmartPLS version 4.0 software. The research results show that the accessibility of financial reports and human resource competency positively affect Zakat's financial accountability. Internal control can strengthen the influence of financial report accessibility on Zakat's financial accountability. However, internal control weakens the influence of human resource competency on Zakat's financial accountability. The results of this research can be used as reference and comparison material for further research. Then, the research results can be used for consideration, input, and thought contribution, especially regarding increasing accountability in zakat financial management.